The influence of electric stimulation on the endurance runners' peripheral and systemic blood flow after local dynamic work - Grunovas, A.; Silinskas, V. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The aim of this study is to access the infkluence of the additional recovery means electro stimulation on peropheral and systemic blood flow after after local dynamic exercise up to inability. ES was applied after local dynamic exercise. The investigations showed that ES increases the velocity of the recovery process, the capacity of muscles also recovers faster. The cardiac putput increased due to the stroke volume and heart rate changes. The ES improved the blood flow to the heart, therefore the stroke volume after the physical exercise returned to the initial level.